MODIFICATION OF CARBON PASTE ELECTRODE WITH NON IMPRINTED POLYMER AND MOLECULARLY IMPRINTED POLY(GLUTAMIC ACID) FOR VOLTAMMETRIC DETERMINATION OF PARACETAMOL - Hafidhoh S N, Sanny
Paracetamol is an analgesic that’s useful in broad range of clinical condition. however, at higher doses it can produce NAPQI which causing acute hepatic necrosis. Therefore it is very important to develop effective analytical methods for paracetamol analysis. One of that methods is voltammetry with carbón paste electrode (CPE) as working electrode. However, CPE gives low current response. CPE modification with NIP (non imprinted polymer) technique and MIP (molecularly imprinted poly(glutamic acid)) technique can increase current response. Modification occured with cyclic voltammetry and determination of paracetamol occured with differential pulse voltammetry. Paracetamol determination with CPK -NIP- MIP (monomer:template composition = 3:1) gives increasing peak current. %RSD of repeated detemination is 13,72% (n=40). The calibration curve at range 100-1000 ?M was the most linear (limit of detection = 2,16 ?M). Result of paracetamol sample determination with CPE-NIP-MIP showed %recovery close to 100%.